Implementasi Pendekatan Deep Learning Melalui Si PONPEL untuk Meningkatkan Pemahaman Konsep Matematika di Sekolah Dasar - Rina Dwi Astuti; Sinta Devi Prastika Putri; Siti Inganah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
The purpose of this study was to evaluate the application of the Deep Learning approach in teaching mathematics in the first grade of addition and subtraction of numbers 1 to 20 in a story problem through the concrete media Si PONPEL and the educational game Quizizz Paper Mode. This technology-based learning is intended to make learning more interactive and enjoyable, but does not require personal digital devices. Qualitative and quantitative data were collected through a mixed-method research design to measure student understanding the result show that the Si PONPEL and Quizizz Paper Mode methods successfully improved students’ understanding of basic mathematical concepts, with an average increase in student scores of 38.33%. In addition, findings from interviews conducted with teachers and students showed that the Si PONPEL concrete media and this technology made students more engaged and motivated to learn. It is hoped that this research will make a significant contribution to creating more inclusive and interactive mathematics kearning in elementary schools.